Does Histologic Chorioamnionitis in Patients With Preterm Premature Rupture of Membranes Depend on Group B Streptococcus Status? [118]. (May 2015) - Patel, Krunal P.; Williams, Shauna F.; Apuzzio, Joseph; Bilinski, Robyn T.; Guirguis, George
Abstract : INTRODUCTION: Histologic chorioamnionitis is a common finding in patients with preterm premature rupture of membranes (PROM). The purpose of this study is to determine whether the rate of histologic chorioamnionitis differs based on group B streptococcus (GBS) carrier status in candidates for expectant management for preterm PROM at less than 34 weeks of gestation. METHODS: A retrospective study was performed of all pregnant women admitted with preterm PROM between 23 0/7 weeks and 33 6/7 days of gestation from January 1, 2005, to June 15, 2014, at our institution. Patients included were candidates for expectant management. Patients were excluded if there was evidence of chorioamnionitis, nonreassuring fetal status or labor at the time of admission, multifetal gestation, if they were human immunodeficiency virus–positive, if GBS cultures were not performed, or if histology was not available. Specimens for GBS analysis were obtained on admission from the lower third of the vagina and rectum. Placental pathology results were compared using Fisher's exact test. RESULTS: One hundred sixty-five patients met inclusion criteria and 56 (33.9%) patients were GBS-positive. Prevalence of histologic chorioamnionitis did not differ between the GBS-positive and GBS-negative groups (66% compared with 63.3%, respectively; P =.86). Clinical chorioamnionitis, wound infection, and maternal and neonatal sepsis did not differ between the GBS-positive and GBS-negative groups, although the rate of endometritis trended higher in the GBS-negative group (13.8% compared with 3.6%, P =.057). CONCLUSION: Group B streptococcus genital tract colonization on admission does not appear to affect the rate of histologic chorioamnionitis in patients with preterm PROM managed conservatively at less than 34 weeks of gestation.